Secret Shame—Male Infertility and Donor Conception in the Wake of Retrospective Legislative Change. (August 2022) - Cosson, Barbara; Dempsey, Deborah; Kelly, Fiona
Historically, sperm donation was shrouded in secrecy to protect the normative family and the perceived vulnerability of infertile men. However, openness about donor conception is increasingly encouraged, in acknowledging that donor-conceived people may benefit from having access to information about their biogenetic origins. Since 2017 in the state of Victoria, Australia, donor-conceived people have been able to access previously anonymous donor records. Drawing on interviews with 17 donor-conceived adults who have come to know their donor through the new laws, this article explores the impact of finding out about the donor on relationships with mothers and fathers, and points to the persistent effects of stigma and shame about donor conception within families. Most of the donor-conceived participants were told about their donor conception in early adulthood. The age range for time of disclosure was mid-teens to early 40s. Most reported that their fathers did not want them to know. In some cases, mothers had disclosed, but sworn them to secrecy. Sensitivity to fathers' feelings fostered a desire among participants to maintain secrecy about his infertility, especially in relation to wider family and friendship networks. Our findings revealed that secrecy about men's infertility is heavily reliant on women's emotional labor to protect ageing infertile fathers' sense of manhood. Coupled with fathers' overt resistance to openness, intergenerational secret keeping is perpetuated in families. Laws supporting openness potentially exacerbate the historical stigma associated with male factor infertility in a culture that continues to conflate virility, fertility, and masculinity.